Evaluating An Academic-Service Partnership on Evidence-Based Practice in Public Health - Gussert, Alaina; Jerdee, Nicole; Stein, Rachel; Conway, Kaitlyn; Hynek, Maddie; Nase, Courtney; Xiong-Yang, Pang (My University, 2015)
The purpose of this study was to utilize student efforts to provide high quality, evidence-based resesarch to promote public health changes and influence policies.
Color poster with text, photographs, and images.
Keywords: Evidence-based research; Public health nursing; Posters